2015
DOI: 10.1186/s40172-014-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

The unhappily unemployed return to work faster

Abstract: This paper shows that job loss is associated with a fall in subjective well-being (SWB). It then looks at how this change in SWB predicts job search and unemployment duration. The findings suggest that those who report feeling hurt by unemployment have shorter unemployment durations. Men who report a loss of SWB are also more likely to look for a job, but women's job search is not affected by the SWB loss. These findings confirm the theoretical prediction from job search theory: search effort and unemployment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…The regional differences in unemployment duration and the influence of business cycles and professional activation programmes could be also examined. Previous analyses confirm strong influence of place of living on unemployment duration [Rotaru 2014;Mavridis 2015].…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The regional differences in unemployment duration and the influence of business cycles and professional activation programmes could be also examined. Previous analyses confirm strong influence of place of living on unemployment duration [Rotaru 2014;Mavridis 2015].…”
Section: Discussionsupporting
confidence: 49%
“…In the case of the influence of sex on unemployment duration quite often it is stated that men have greater chances of getting work [Stetsenko 2003;Daras and Jerzak 2005, BAEL, 1993. Some authors found that women have higher chances of getting work [Bieszk-Stolorz and Markowicz 2011;Grogan and van den Berg 2001;Mavridis 2015;Landmesser 2013]. Quite rarely results confirming no influence of sex on unemployment duration are presented [Grzenda 2012, data: Budgets of Households, 2008.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…Clark (2003a) also uses BHPS data to show that the size of the drop in GHQ upon entering unemployment predicts how much the individual searches for a new job, and how fast they leave unemployment: those who suffered the largest well-being drop search more and leave the fastest. This result has been updated by Mavridis (2015), and replicated using data on life satisfaction in SOEP data by .…”
Section: Behavioural Beauty Contests: Which Measure Predicts Best?mentioning
confidence: 92%